Effects of Initial Abstinence and Programmed Lapses on The Relative Reinforcing Effects of Cigarette Smoking - Chivers, Laura L (The Society for the Experimental Analysis of Behavior, 2008)
Fifty-eight smokers received abstinence-contingent monetary payments for 1 (n  =  15) or 14 (n  =  43) days. Those who received contingent payments for 14 days also received 0, 1, or 8 experimenter-delivered cigarette puffs on 5 evenings. The relative reinforcing effects of smoking were assessed in a 3-hr session on the final study day, when participants made 20 choices between smoking or money. The reinforcement contingencies exerted robust control over smoking, and programmed smoking lapses produced few discernible effects. These results further illustrate the robust control that reinforcement contingencies can exert over cigarette smoking and suggest that any effects of lapses on the relative reinforcing effects of smoking are modest under conditions involving abstinence-contingent reinforcement contingencies.